Design Of Digital Imaging System Using Digital Signal Processor (DSP) - Yeoh, Siew Lee (Universiti Sains Malaysia, 2006)
The objective of this project is to present the design and analysis of a camera module system which this system will be able to capture still images from camera, process these digital images and then display through the computer screen. The digital imaging microcontroller system using digital signal processor (DSP) has been designed and developed. This microcontroller can be distributed into four parts. The main part was contributed by the DSP chipset which act as a centre processing unit (CPU) to control all the processing of images data flow. The second part will be the voltage regulator part to step down the 5V to 3.3V and 1.8V for DSP source power purposes and also to step down to 2.8V for the camera source power purposes. The third part make up of all the logic devices as to store and process the images data. The final part will be treated as transmit and receive control system for the serial communication in between microcontroller system and computer. In addition, this project also analyzes the application of digital image processing using digital signal processor starter kit (DSK). Implementation of the design and analysis of this project will be reported in details. Finally, further analysis and the real time data to image conversion form cannot be executed but the results regarding the processing of the digital image data during the analysis will be discussed in this project.